Ultrasound-guided endoscopic endonasal resection of sellar and suprasellar craniopharyngiomas - Finger, Guilherme; Wu, Kyle C.; Godil, Sanyia S.; Carrau, Ricardo L.; Hardesty, Douglas; Prevedello, Daniel M. (Frontiers in Surgery, 2023)
Introduction: Optimal planning and minimally invasive surgical approach are essential to complete craniopharyngiomas (CP) resection with limited postoperative morbidity. Given the nature of craniopharyngioma recurrence, complete resection of the neoplasm is crucial. Since CP arise from the pituitary stalk and may grow anteriorly or laterally, some cases require an extended endonasal craniotomy. The extension of the craniotomy is crucial to expose the whole tumor and to make its dissection from the surrounding structures feasible. In order to guide the extension of the approach, the intraoperative use of ultrasound is helpful for the surgeons. The objective of this paper is to describe and to demonstrate the applicability of the utilization of intraoperative ultrasound (US) guidance for planning and confirmation of craniopharyngioma resection in EES. Method: The authors selected one operative video of a sellar-suprassellar craniopharyngioma gross-totally resected by EES. The authors demonstrate the extended sellar craniotomy, the anatomic landmarks that guide bone drilling and dural opening, the aspect of the intraoperative real time US, tumor resection and dissection from the surrounding structures. Results: The solid component of the tumor was mostly isoechogenic in texture compared to the anterior pituitary gland, with several wide spread hyperechogenic images corresponding to calcifications and hypoechogenic vesicles corresponding to cysts inside the CF (“salt-and-pepper” pattern). Discussion: The intraoperative endonasal US is a new surgical tool that allows for real-time active imaging for skull base procedures, such as sellar region tumors. Besides tumor evaluation, the intraoperative US helps the neurosurgeon to determine the size of craniotomy, to anticipate the relation between the tumor and vascular structures and to guide the best strategy for gross-total resection of the tumor. Conclusion: The EES allows a straight access to the craniopharyngiomas located in the sellar region or that grow anteriorly or superiorly. This approach allows the surgeon to dissect the tumor with minimal manipulation of the surrounding structures, when compared to craniotomy approaches. In order to accomplish that, the use of intraoperative endonasal ultrasound helps the neurosurgeon to perform the most suitable strategy, optimizing the rate of success.